Stream Biofilm Responses to Flow Intermittency: From Cells to Ecosystems - Sabater, Sergi; Timoner, Xisca; Borrego, Carles; Acuña, Vicenç (Frontiers in Environmental Science, 2016)
Temporary streams are characterized by the alternation of dry and wet hydrological phases, creating both a harsh environment for the biota as well as a high diversity of opportunities for adaptation. These systems are eminently microbial-based during several of these hydrological phases, and those growing on all solid substrata (biofilms) accordingly change their physical structure and community composition. Biofilms experience large decreases on cell densities and biomass, both of bacteria and algae, during dryness. Algal and bacterial communities show remarkable decreases in their diversity, at least locally (at the habitat scale). Biofilms also respond with significant physiological plasticity to each of the hydrological changes. The decreasing humidity of the substrata through the drying process, and the changing quantity and quality of organic matter and nutrients available in the stream during that process, causes unequal responses on the biofilm bacteria and algae. Biofilm algae are affected faster than bacteria by the hydric stress, and as a result the ecosystem respiration resists longer than gross primary production to the increasing duration of flow intermittency. This response implies enhancing ecosystem heterotrophy, a pattern that can be exacerbated in temporary streams suffering of longer dry periods under global change.